O processo e o significado de elaborar princípios de convivência do trabalho coletivo à humanização: diálogos com Paulo Freire - Gonçalves, Lílian Dilli (2012)
This dissertation constitutes a study focused on the construction and reconstruction of principles of coexistence by the students of the Instituto Federal de Educação, Ciência e Tecnologia Sul-Rio-Grandense, Charqueadas Campus. The main objective of the investigation is to unveil the meaning of this collective construction process for learners. It is a qualitative study, which aims to interpret the reports given by the learners, relating their narrations to the theoretical support and the investigation problem as well. The data have been produced via a semi-structured interview, observing not only their answers, but also the students body language and behavior, conducting the data analysis based on the theoretical references of the humanizing education and collective work, taking into account, fundamentally, Paulo Freire s considerations. The investigation verified to what extent the collective work motivated the development of new relationships among them, besides confirming that the students involvement in the construction of the principles contributed to a new attitude towards disciplinary issues. This study seeks to contribute with the discussions on elaboration processes based on collective work with students. The findings point out the strengthening of the affective relations, the value given to collective work, the importance of the dialogue and of listening to others.